2005
DOI: 10.1016/j.febslet.2005.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Aβ(31–35) and Aβ(25–35) fragments of amyloid beta‐protein induce cellular death through apoptotic signals: Role of the redox state of methionine‐35

Abstract: In order to clarify the basis of neuronal toxicity exerted by the shortest active peptides of amyloid beta-protein (Ab), the toxic effects of Ab(31-35) and Ab(25-35) peptides on isolated rat brain mitochondria were investigated. The results show that exposure of isolated rat brain mitochondria to and Ab(25-35) peptides determines: (i) release of cytochrome c; (ii) mitochondrial swelling and (iii) a significant reduction in mitochondrial oxygen consumption. In contrast, the amplitude of these events resulted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
176
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(192 citation statements)
references
References 44 publications
11
176
0
Order By: Relevance
“…2833 Aβ(25–35) is an amphipathic peptide with similar aggregation propensity and toxicity to the full length Aβ(1–42). 34,35 Takashima et al 27 have shown that embryonic rat hippocampal neurons undergo progressive degeneration and that Tau phosphorylation is enhanced after exposure to Aβ(25–35), similar to the result obtained with Aβ(1–40) by Busciglio and co-workers. 25 Tau(273–284) is in the second repeat (R2) of MTBR and encompasses the PHF6* hexapeptide (VQIINK), one of the two hexapeptides known to play an important role in Tau aggregation.…”
Section: Introductionsupporting
confidence: 67%
“…2833 Aβ(25–35) is an amphipathic peptide with similar aggregation propensity and toxicity to the full length Aβ(1–42). 34,35 Takashima et al 27 have shown that embryonic rat hippocampal neurons undergo progressive degeneration and that Tau phosphorylation is enhanced after exposure to Aβ(25–35), similar to the result obtained with Aβ(1–40) by Busciglio and co-workers. 25 Tau(273–284) is in the second repeat (R2) of MTBR and encompasses the PHF6* hexapeptide (VQIINK), one of the two hexapeptides known to play an important role in Tau aggregation.…”
Section: Introductionsupporting
confidence: 67%
“…Among the Ab fragments studied so far, the Ab25-35 peptide represents the shortest fragment of Ab processed in vivo by brain proteases [15]. Therefore, this peptide exhibits significant levels of molecular aggregation, retaining the toxicity of the fulllength peptide, although it is lacking of the metal binding sites [16]. It has been proposed that Ab25-35 peptide represents the biologically active region of Ab1-42 [17].…”
Section: Introductionmentioning
confidence: 99%
“…78 It is well known that the oxidation state of this methionine strongly modifies the properties of A. 79,80 It significantly impairs the rate of amyloid formation, alters the fibril morphology, and modifies the neurotoxic features of A. As the oxidation of Met35 modifies A42 oligomerization, 81 it was concluded that Met35 is directly involved in formation of A42 paranuclei, probably through an intermolecular interaction between Met35 and Ile41.…”
mentioning
confidence: 98%